A Comparative Study of Reproductive Health and Awareness Level of Students in Different Faculties - SUBRAMANIAN, RAMAA (Advances in Social Sciences Research Journal, 2020)
World Health Organization (WHO) defines adolescence as the period of life between 10 and 19 years of age. The adolescent experiences changes in various dimensions which includes not only physical but also emotional, psychological, social, and mental change and growth. Physiological changes lead to sexual maturity and usually occur during the first several years of this period. Majority of adolescents still do not have access to information and education on sexuality, reproduction, and sexual and reproductive health and rights, nor do they have access to preventive and curative service. Due to lack of adequate knowledge they are subject to many problems which pose threat to their healthy life. Pregnancy during adolescence is very serious problem in our country. This study aims to find the level of reproductive health and awareness among girls. Also aims to find whether there is any relationship between the faculty in which they study and their awareness level. Primary data was collected from college going girls in the first year of under graduate programme of all three basic faculties.